Discovery of an established population of a non-native species of Viviparidae (Caenogastropoda) in Argentina - Ovando, Ximena Maria Constanza (2012)
Discovery of an established population of Sinotaia quadrata (Benson, 1842) in a river and reservoir inArgentina is reported, representing the first report of a Recent viviparid species in South America. Viviparidsare a family of freshwater snails occurring nearly worldwide. A study of the shell and aspects of the anatomyof S. quadrata are presented. It is distinguished from other native taxa by its large shell size, presence ofa blackish axial band on the columellar side of the aperture and two to three carina on the body whorl.The invasive species Physa acuta Draparnaud, 1805 (Physidae) and Corbicula fluminea (Müller, 1774)(Corbiculidae) also inhabit the same sites as Sinotaia quadrata. Co-occurring native species of molluscsare Pomacea canaliculata (Lamarck, 1822) (Ampullariidae) and Biomphalaria tenagophila (d´Orbigny, 1835)(Planorbidae). This record increases the total number of invasive gastropods in Argentina to six.